Psychometric properties of the Iranian version of Wijma delivery expectancy / experience questionnaire in women who experience fear of childbirth: version B - Zahra Abbaspoor; Mohammad Hosein Haghighizadeh; Parvin Abedi (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: This study aimed to explore the psychometric properties of the Wijma delivery expectancy / experience questionnaire (WDEQ-B): Iranian version. Methods: In this cross-sectional study 660 women in the postpartum period were recruited in Ahvaz, Iran from May 2017 to October 2017. A sociodemographic questionnaire, a WDEQ - B questionnaire, Beck depression (BAI) and depression, stress, and anxiety (DASS) questionnaires were used to gather information. The experts used the forward-backward process to the translation of the WDEQ - B. The exploratory factor analyses, Cronbach's alpha, Pearson correlation, and independent t-test were used to analyze data. Results: Cronbach's alpha for all factors except for concerns for the baby (α=0.50) and lack of positive behaviors (α=0.60), was more than 0.71. The W-DEQ - B was found to have six factors including lack of positive feelings, fear and pain, concerns about childbirth, loneliness, lack of positive behaviors, and concerns for the baby. They explained 52% of the overall variance and there was a positive correlation between WDEQ-B and BAI, DASS questionnaires. Conclusions: Persian version of WDEQ-B is a valid and reliable questionnaire to use among Iranian women.